Multi‐disciplinary, simulation‐based, standardised trauma team training within the Victorian State Trauma System. (1st September 2022) - Fitzgerald, Mark C; Noonan, Michael; Lim, Emma; Mathew, Joseph K; Boo, Ellaine; Stergiou, Helen E; Kim, Yesul; Reilly, Stephanie; Groombridge, Christopher; Maini, Amit; Williams, Kim; Mitra, Biswadev
Abstract: Objective: Inconsistency in the structure and function of team‐based major trauma reception and resuscitation is common. A standardised trauma team training programme was initiated to improve quality and consistency among trauma teams across a large, mature trauma system. The aim of this manuscript is to outline the programme and report on the initial perception of participants. Methods: The Alfred Trauma Team Reception and Resuscitation Training (TTRRT) programme commenced in March 2019. Participants included critical care and surgical craft group members commonly involved in trauma teams. Training was site‐specific and included rural, urban and tertiary referral centres. The programme consisted of prescribed pre‐learning, didactic lectures, skill stations and simulated team‐based scenarios. Participant perceptions of the programme were collected before and after the programme for analysis. Results: The TTRRT was delivered to 252 participants and 120 responses were received. Significant improvement in participant‐reported confidence was identified across all key topic areas. There was also a significant increase in both confidence and clinical exposure to trauma team leadership roles after participation in the programme (from 53 [44.2%] to 74 [61.7%; P = 0.007]). This finding was independent of clinician experience. Conclusions: A team‐based trauma reception and resuscitation education programme, introduced in a large, mature trauma system led to positive participant‐reported outcomes in clinical confidence and real‐life team leadership participation. Wider implementation combined with longitudinal data collection will facilitate correlation with patient and staff‐centred outcomes. Abstract : A team‐based trauma reception and resuscitation education programme, introduced in a large, mature trauma system led to positive participant‐reported outcomes in clinical confidence and real‐life team leadership participation.